PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF NONI–LEMONGRASS POWDERED DRINK AT DIFFERENT JUICE RATIOS - Khansa Tasya Nabila; Raswen Efendi; Rahmadini Payla Juarsa; Annisa Nazifa Salman; Anik Nur Habyba (SAGU, 2026)
Commercial noni powder generally has a bitter taste and an unpleasant aroma; therefore, lemongrass was added to improve its sensory characteristics. The purpose of this research was to obtain the best formulation for the physicochemical and sensory characteristics of noni juice and lemongrass juice powder drinks in accordance with SNI 01-4320-1996. The treatments consisted of MS1 (noni juice 85% and lemongrass juice 15%), MS2 (noni juice 75% and lemongrass juice 25%), MS3 (noni juice 65% and lemongrass juice 35%), and MS4 (noni juice 55% and lemongrass juice 45%). Data were statistically analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level. The result showed the juice ratio had a significant effect on yield, moisture content, ash content, total dissolved solids, dissolution time, antioxidant activity, and organoleptic. The optimum treatment in this research was MS3 (noni juice 65% and lemongrass juice 35%), which meets the quality requirements for powdered drinks as specified in SNI 01-4320-1996. The powdered drinks with the MS3 treatment had a yield of 43,26%, moisture content of 1,91%, ash content of 1,54%, total dissolved solids of 15,20°Brix, dissolution time of 25,92 seconds, and antioxidant activity of 67,48%. The product had slightly cloudy, a slightly noni aroma, a slightly lemongrass aroma, a slightly noni taste, a slightly lemongrass aroma, and a slightly lemongrass taste. The MS3 treatment has met the quality requirements for powdered drinks in accordance with SNI 01-4320-1996.